Analisa kandungan klorin (Cl2) pada beberapa merek pembalut wanita yang beredar di pusat perbelanjaan di kota medan - Suryasih Mustika Nasution; evi naria; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Abstrak Analysis of chlorine (Cl2) content in some brands of sanitary napkins in circulation at the shopping center in the city of Medan. Sanitary napkin is a device used by women when menstruation which serves to absorb the blood and is also commonly used sanitary napkins everyday to provide comfort to the female reproductive organs, which in the production process using bleach pads, one of which is chlorine (Cl2) . Chlorine is a greenish yellow gas, which along with technological advances in the manufacture of sanitary napkins from recycled materials using chemicals to clean it and also use of chlorine materials so that the clean white napkin.The purpose of the study to determine the chlorine content in some brands of sanitary napkins in circulation in several shopping centers in the city of Medan. This study is a descriptive survey. Object of study is 10 (ten) samples of sanitary napkins and then examined with a field area of health laboratory titration method.Based on the results of the study there were 4 samples containing chlorine napkins. 4 sample is then analyzed quantitatively to measure the levels of chlorine contained therein, it is known that the chlorine levels to vary from 4 samples, the levels found in the studied range of sanitary napkin 0.1 gr - 0.4 gr.The conclusion of this study is that the chlorine content contained in a sanitary napkin that has been studied, which can cause disturbances in the female reproductive organs. According to the Minister Regulation. 472/Menkes/Per/V/1996 about the use of hazardous substances for health. Advised consumers to be more selective in choosing a sanitary napkin to wear and consumers should pay attention to the composition and permit the sanitary napkin packaging before buying. Keywords: Sanitary napkin, Chlorine, Shopping center